Hubungan Dimensi Parenting dengan Indeks Karies Gigi pada Anak Kelas 5 di Sekolah Dasar 136 Sukawarna Bandung - Putri Nur Shakira Binti Azhar; Ellen Theresia; Linda Sari Sembiring (Maranatha Christian University, 2023)
Parenting is a form of interaction between parents and children with the aim of helping their children to develop. Parenting style is formed from the dimensions of responsiveness and demandingness. Parents can affect their children's dental health such as oral hygiene, dietary practices, and tooth growth patterns through attention and rules given to their children. The aim of this study is to determine the correlation between parenting dimensions and dental caries index of 5th grade student at Elementary School 136 Sukawarna. The study was conducted as a whole sampling in 5th grade student involving 105 children. This study used a questionnaire containing 38 questions about children's appreciation of their parents’ responsiveness and demandingness and an observation was conducted to examine the dental caries index. The results of this study indicate the correlation value (r) between responsiveness with def-t index 0.642, the correlation value (r) between demandingness with def-t index 0.545, the correlation value (r) between responsiveness and the DMF-T index 0.323, the correlation value (r ) between demandingness and DMF-T index 0.410 which all result shows significant correlation with different strengths of correlation. From this study, we can conclude that there is a significant correlation between parenting dimensions and dental caries index of 5th grade students at Elementary School 136 Sukawarna. The researcher proposes a suggestion to study the contribution of parenting style to dental caries index of the children in hope of providing input related to psychoeducation for parents to play a role in children's dental health and to be conducted on different development period samples or broader samples. Keywords: parenting dimension, dental caries index, middle childhood